Social enrichment affects fish growth and aggression depending on fish species: Applications for aquaculture - Zonghang Zhang; Yiqiu Fu; Hancheng Zhao; Xiumei Zhang (Frontiers in Marine Science, 2022)
Growth performance and aggressive behavior are important measures in fish aquaculture. So, from the perspectives of food production and fish welfare, it is always valuable to increase growth rate and reduce fish aggression efficiently. Physical enrichment has been verified to be a promising method to improve fish welfare. But there is very scarce knowledge about social enrichment, which is an important category of environmental enrichment. In the wild, several fish species often inhabit the same habitat, inevitably experiencing social interactions with each other. From the perspective of nature-based welfare, such social interactions are essential for fish ontogenesis, and deprivation of this social environment may damage fish welfare. Here, we focused on two typical territorial fish species, black rockfish (Sebastes schlegelii) and fat greenling (Hexagrammos otakii), which are often found to inhabit the same area in the wild, in contrast, traditional fish farms simultaneously rear them with the monoculture mode. And we explored the effects of social enrichment (through introducing different numbers of two fishes into the same environment) on their growth and aggression. The results showed that introducing rockfish as a stimulus significantly increased the growth performance of greenling (especially the medium and high enrichment amounts), but social enrichment did not present such effects on the growth of rockfish. Proper social enrichment also significantly decreased the intraspecies aggression both among rockfish and among greenling. Moreover, greenling expressed significantly more aggressive behavior toward rockfish (i.e., the interspecies aggression from greenling toward rockfish) than in reverse. Finally, the average distribution proportion in central areas and standard metabolic rate of greenling were significantly higher than those of rockfish. These results suggest that proper social enrichment is an effective method to decrease aggression and increase growth of the fat greenling, but this improvement is accompanied by a compromised rockfish welfare. This study will promote the application of environmental enrichment strategy on improving the welfare of specific fish species and provide fundamental information for reducing fish aggression and improving fish growth in aquaculture. Further research is needed to optimize the combinations of fish species for practical applications in aquaculture.